Cigarettes and capacity: a case study in enforced smoking cessation. Issue 1 (January 2016) - Cooney, Gary; Murdie, Douglas; Moffoot, Anthony
Abstract : The antipsychotic agent clozapine is frequently used in patients with treatment‐resistant psychotic illnesses such as schizophrenia and schizoaffective disorder. It is well established that cigarette smoking reduces circulating levels of clozapine, thereby limiting its efficacy. Here, Dr Cooney et al. report the unprecedented step in applying to the Courts for a mandate through the Adults with Incapacity Act (Scotland) for a patient to follow an enforced smoking cessation program in the hope that this would improve her psychiatric symptoms. The authors illustrate how solutions to medical problems can be achieved by looking beyond biomedical models.